Setting up a diagram process for the elaboration of a new plant‐based beverage from Pinus halepensis seeds: Selection of unit operations and their conditions. (28th November 2021) - Abbou, Amina; Kadri, Nabil; Servent, Adrien; Ricci, Julien; Madani, Khodir; Dornier, Manuel; Collignan, Antoine; Achir, Nawel
Abstract: Aleppo pine seeds are a potential candidate for the production of nondairy milk due to their high protein (26%) and lipid (37%) content and their availability. For the first time, this study presents the implementation of a manufacturing scheme from seeds to final product, including pre‐extraction, extraction, and post‐extraction (physical and microbiological stabilization), using a 2 (7‐4) fractional factorial screening design. The seven factors were seed soaking time, grinding time, temperature and seed/water ratio during extraction, xanthan gum concentration, homogenization pressure, and pasteurization temperature. Beverage quality analysis consisted of measurements of chemical composition, color, stability, and rheological behavior. The results of experimental design showed that the dry matter as well as the lipid and protein contents increased significantly by increasing the ratio (grain/water) and the grinding time. On the other hand, the extraction temperature led to a better extraction of lipids but a lower extraction of proteins. Regarding stability, xanthan gum had a negative effect, while homogenization pressure and pasteurization temperature showed their effectiveness in decreasing the particle size and increasing the physical stability of the product. Practical applications: Plant‐based drinks, also called plant milks, are interesting alternatives to animal milk. They have similar organoleptic properties but are more sustainable and offer very different nutritional composition depending on the plant used. As the consumers demand is constantly increasing, setting up fabrication processes from new plant sources is relevant. Aleppo pine seeds are a potential matrix for the production of vegetable beverages because they are very nutritious and available in the entire Mediterranean area. This study presents the setting up of a fabrication diagram of a plant‐based beverage made from Aleppo pine seeds. Seven production parameters were tested, including pre‐extraction (seed conditioning), extraction, and post‐extraction (physical and microbiological stabilization), thanks to a fractional factorial 2 (7‐4) screening design. The best conditions enabled the production of a final beverage comparable to other commercialized plant‐based beverages in terms of nutritional and organoleptic quality. Abstract :